Structuring the WR Soepratman Street Corridor in the Context of Locality - Juwito, Rizqiyah Safitri; Sari, Renitha; Fatona, Geby (MultiTech Publisher, 2024)
The road corridor of WR Soepratman Street in Bengkulu City is located within the education, trade and service sectors. These sectors have cultures that contrast with each other. These cultural differences are certainly not favorable in terms of functionality. People in the education sector really need the trade and service sector to support educational contributions. Meanwhile, trade and services need the education sector to improve the economy. Education cannot be separated from culture, even the quality of education is a measure of a nation's culture. Trade and services are actually fulfilled by educated people. Based on the research, there is an intersection of the two sectors in a commercial and cultural frame, without changing the functions that have been formed by maximizing the combination of the two sector functions and blurring the existing gaps.